KEMAMPUAN PENALARAN ADAPTIF SISWA DALAM MENYELESAIKAN SOAL KONTEKSTUAL DITINJAU DARI ADVERSITY QUOTIENT - Nurhaissyah Nurhaissyah; Edy Yusmin; Mohammad Rif'at (Jurnal AlphaEuclidEdu, 2023)
This research aims to describe students' adaptive reasoning abilities in solving contextual problems on absolute value topic based on adversity quotient (AQ) of climber, camper and quitter types at SMAN 1 Teluk Keramat. The method used in this research is descriptive. Based on the results of the research. This research subjects were six students at X MIPA 2 in the 2021/2022 academic year which three subjects have AQ of climber and  three subjects have AQ of camper. Based on the results of data analysis, it was found that the adaptive reasoning abilities of students who have the AQ climber type have different abilities from each other, two of the three subjects of the AQ climber type are able to answer all indicators of adaptive reasoning, and the other one is only able to answer four reasoning indicators; the adaptive reasoning ability of students who have the AQ camper type also has different abilities from each other but three subjects from the AQ Camper type are able to fulfill three of five indicators of adaptive reasoning; the adaptive reasoning ability of students who have the AQ quitter type was not found in this research.